Orthopaedic Trainees Retain Knowledge After a Partner Abuse Course: An Education Study - Madden, Kim (Clin Orthop Relat Res, 2015)
INTRODUCTION: Intimate partner violence (IPV) is a serious global issue that results in a large number of injuries and deaths among women. Educating clinicians about IPV can help providers identify, prevent, and treat victims, and, ultimately, improve care for victims of abuse. We sought to determine the effect of a half-day educational course on IPV for orthopaedic surgical trainees on knowledge and attitudes. QUESTIONS/PURPOSES: We asked (1) whether a half-day educational course on IPV can improve orthopaedic surgical trainees’ knowledge and (2) attitudes regarding IPV; and (3) whether a course on IPV can be accepted and viewed as valuable by trainees? METHODS: Using published research on IPV in patients with musculoskeletal injuries, we developed a half-day educational course. The curriculum included lectures and discussion regarding the basics of IPV, the current state of IPV research, what to do when a patient is a victim or perpetrator, and the orthopaedic surgeon’s role in recognizing, preventing, and assisting with IPV. All 33 course participants (30 men and three women), all orthopaedic surgical trainees, completed a questionnaire that included general true or false or agree or disagree statements regarding their knowledge, attitudes, and practices of IPV in the musculoskeletal setting; the questionnaire also included a knowledge test of 25 true or false statements. The questionnaire was administered immediately before, immediately after, and 3 months after the course; 76% (25 of 33) took the test immediately after the course and 82% (27 of 33) completed the test at 3 months. Participant knowledge scores were compared across the three different times to determine the effect of the course. RESULTS: Participants increased their knowledge after the course, and the increased knowledge was retained at retesting at 3 months; the mean percentage of correct answers before the course was 57%, which increased to 73% after the course, and was 68% 3 months later (F = 9.505; p = 0.001). Before the course, most of the course participants (30 of 32; 94%) agreed that IPV is an important issue; agreement increased to 100% immediately after the course. The largest change in attitude was in response to the statement: “I am skeptical that the health care system has the resources to screen for IPV.” Before the course, 53% (17 of 32) of trainees endorsed this statement, but the percent decreased to 36% (nine of 25) after the course and remained low at 33% (nine of 27), at the 3-month test. CONCLUSIONS: Our findings show that a short course on IPV in patients with musculoskeletal injuries led to an improvement and retention of knowledge 3 months after the course. Based on our findings, we recommend that IPV education be integrated in training programs for orthopaedic surgeons. Future projects should focus on developing and implementing a sustainable education program that can affect practice for healthcare professionals and trainees in multiple clinical settings. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-015-4325-7) contains supplementary material, which is available to authorized users.